COVID-19 humoral response - Adam Tworek; Andrzej Rydzewski; Grażyna Rydzewska; Martyna Głuszek-Osuch; Konrad Lewandowski (Studia Medyczne, 2023)
This article reviews studies on SARS-CoV-2 antibodies, including neutralizing antibodies (NAbs) and post-vaccination response. The SARS-CoV-2 virus is closely related to SARS-CoV and MERS-CoV, sharing 79% and 50% of its genome sequence with them, respectively. Antibodies are crucial in identifying and destroying pathogens such as viruses, and understanding virus-specific antibodies can help end pandemics quickly. The SARS-CoV-2 virus uses the spike protein to enter human cells via the angiotensin-converting enzyme 2 receptor (ACE2). The immune response to the virus involves various components, including dendritic cells, T cells, B cells, and NAbs. Seroconversion, antibody kinetics, and immune response after COVID-19 vaccination are essential factors in understanding the virus and developing treatments. Neutralizing antibody therapies have been explored as potential treatments, but the emergence of viral variants challenges their long-term development. Lessons learned from antibody-based therapies can influence future strategies for treating emerging infectious diseases.